2014
DOI: 10.4049/jimmunol.1400993
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for CCR4 and CCR7 during the Development of Innate and Adaptive αβT Cells in the Adult Thymus

Abstract: αβT cell development depends upon serial migration of thymocyte precursors through cortical and medullary microenvironments, enabling specialized stromal cells to provide important signals at specific stages of their development. Although conventional αβT cells are subject to clonal deletion in the medulla, entry into the thymus medulla also fosters αβT cell differentiation. For example, during postnatal periods, the medulla is involved in the intrathymic generation of multiple αβT cell lineages, notably the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 41 publications
(74 reference statements)
6
80
0
Order By: Relevance
“…Interestingly, this may reflect a minor role for CCR4 in an earlier developmental stage. Aire-dependent expression of CCR4 has been shown to occur during the development of multiple αβ T cell lineages in the thymus, although CCR4 was not unanimously found to be required for T cell development in these studies (32,33). Thus, CCR4 may play a role in the T cell lineage at the common lymphocyte progenitor stage, during thymic emigration, or even at the level of systemic circulation.…”
Section: Discussionmentioning
confidence: 65%
“…Interestingly, this may reflect a minor role for CCR4 in an earlier developmental stage. Aire-dependent expression of CCR4 has been shown to occur during the development of multiple αβ T cell lineages in the thymus, although CCR4 was not unanimously found to be required for T cell development in these studies (32,33). Thus, CCR4 may play a role in the T cell lineage at the common lymphocyte progenitor stage, during thymic emigration, or even at the level of systemic circulation.…”
Section: Discussionmentioning
confidence: 65%
“…We found that T cell maturation was independent of migration or egress as SP thymocytes from CD4-cre HDAC3 cKO mice regulate expression of CCR4, CCR7, CCR9 and S1P1 as expected (Figure 4). Conversely, CCR7/CCR4 double KO mice which do not migrate into the medulla display normal maturation of conventional CD4 SP thymocytes, although the development of nTreg and iNKT cells is severely curtailed (5). Mice deficient in S1PR1 or treated with FTY720 show an accumulation of CD24 lo Qa2 hi mature SP thymocytes (8).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, iNKT cell development depends on normal thymus medulla development and interaction with mTECs. Expression of the chemokine receptor CCR7 enables developing iNKT cells to enter the thymic medulla [67] and gain access to mTECs, which play an important role by providing IL-15 transpresentation [47] necessary to the complete development of iNKT1 cells. Because iNKT2 and iNKT17 cells were also found within the medulla [7 •• ], it is likely that other chemokine receptors regulate localization as well.…”
Section: Cell Extrinsic Signalsmentioning
confidence: 99%